Consumption and Savings with Unemployment Risk : Implications for Optimal Employment Contracts - Christopher A. Pissarides (Institute for the Study of Labor (IZA), 2004)
This paper derives optimal employment contracts when workers are risk averse and there are employment and unemployment risks. Without income insurance, consumption rises during employment and falls during unemployment. Optimal employment contracts offer severance compensation and sometimes give notice before dismissal. Severance compensation smoothes consumption during employment but dismissal delays insure partially against the unemployment risk because of moral hazard. During the delay consumption falls to give incentives to the worker to search for another job. No dismissal delays are optimal if exogenous unemployment compensation is sufficiently generous.
Keywords: E24; J32; J33; E21; 330; employment risk; unemployment risk; severance compensation; notice of dismissal; Arbeitsvertrag; Arbeitslosenversicherung; Arbeitslosigkeit; Risiko; Konsum; Arbeitskräfte; Arbeitsmarkttheorie